The Livestock Sector in the Turkish Republic of Northern Cyprus: An Examination of Red Meat Sector - Sertoglu, Kamil; Esendagli, Irfan (International Journal of Economics and Financial Issues, 2023)
This study generally analyses the livestock sector in the TRNC and the red meat sector in particular. The historical overview and economic structure of the TRNC show the importance of the agricultural sector for the TRNC. In order to understand the red meat sector in general, first the international red meat sector is examined shortly and then the red meat sector in the TRNC is analysed. The research data rely on a descriptive analysis based on the interpretation of primary and secondary data from the official websites of the Ministry of Agriculture of Northern Cyprus and Food and Agriculture Organization of the United Nations (FAO). TRNC does not have a liberal economy and import of red meat is strictly forbidden to the country. However, recently, discussions regarding liberalising the import of red meat led to further discussion of the problems experienced in red meat production and the factors affecting costs of production. The decision to import red meat supports the depth of existing problems in this field today. This study aims to reveal the necessity of policies that will bring possible solutions to overcome the structural problems in the red meat sector.